Magnetic Resonance Imaging of the Liver: a Move Towards Function and Quantification - Caseiro-Alves, Filipe (2020)
From an invisible organ to one of the most explored non-invasively, the liver is, today, one of the cornerstones for current cross-sectional imaging techniques and minimally invasive procedures. After the achievements of US, CT and more recently MRI, in providing highly accurate morphological and structural information about the organ, a significant scientific development has gain momentum for the last decades, coupling morphology to liver function and contributing far most to what we know today as precision medicine.